Amorphous Polymer-Phospholipid Solid Dispersions for the Co-Delivery of Curcumin and Piperine Prepared via Hot-Melt Extrusion - Kamil Wdowiak; Andrzej Miklaszewski; Judyta Cielecka-Piontek (MDPI AG, 2024)
Curcumin and piperine are plant compounds known for their health-promoting properties, but their use in the prevention or treatment of various diseases is limited by their poor solubility. To overcome this drawback, the curcumin-piperine amorphous polymer-phospholipid dispersions were prepared by hot melt extrusion technology. X-ray powder diffraction indicated the formation of amorphous systems. Differential scanning calorimetry confirmed amorphization and provided information on the good miscibility of the active compound-polymer-phospholipid dispersions. Owing to Fourier-transform infrared spectroscopy, the intermolecular interactions in systems were investigated. In the biopharmaceutical properties assessment, the improvement in solubility as well as the maintenance of the supersaturation state were confirmed. Moreover, PAMPA models simulating the gastrointestinal tract and blood-brain barrier showed enhanced permeability of active compounds presented in dispersions compared to the crystalline form of individual compounds. The presented paper suggests that polymer-phospholipid dispersions advantageously impact the bioaccessibility of poorly soluble active compounds.